Projections of population exposure to hot and dry events in the end of the 21st century on the Iberian Peninsula - Bento, Virgílio A.; Lima, Daniela C. A.; Russo, Ana (Frontiers in Climate, 2025)
The Iberian Peninsula (IP) is anticipated to undergo future shifts in precipitation patterns and an increased occurrence of hot and dry extreme (HDE) weather events, including droughts and heatwaves. Such events pose substantial risks to the region’s population and ecosystems, particularly amidst evolving demographic dynamics marked by an overall population decrease and contrasting growth in urban areas. This study evaluates population exposure to HDEs in the IP, comparing projected conditions for the late 21st century with the historical period (1971–2000). The Standardized Precipitation-Evapotranspiration Index (SPEI) is used to quantify droughts’ duration and the number of warm months to assess the frequency of extreme heat events. Two representative concentration pathways (RCPs), specifically RCP4.5 and RCP8.5, are considered to represent distinct greenhouse gas emission scenarios. This research reveals a significant projected increase in population exposure to both drought and warm months across the entire IP by the century’s end, with climate change identified as the primary driver of this escalation. Certain regions will experience a particularly drastic surge in drought exposure, while exposure to warm months may exceed 500% in some cases. Climate change’s impact on exposure surpasses that of population change, and the interplay between climate and population changes predominantly contributes negatively across all Iberian regions. These findings are expected to provide valuable insights for policymakers, planners, and stakeholders, guiding the development of targeted adaptation strategies and resource allocation. This proactive approach aims to enhance the resilience of vulnerable communities and ecosystems in response to the evolving climatic conditions.